XL4C4D - Adding the Graph Transformation Language XL to CINEMA 4D - Kniemeyer, Ole; Kurth, Winfried (Electronic Communications of the EASST, 2013)
A plug-in for the 3D modeling application CINEMA 4D is presented which allows to use the graph transformation language XL to transform the 3D scene graph of CINEMA 4D. XL extends Java by graph query and rewrite facilities via a data model interface, the default rewrite mechanism is that of relational growth grammars which are based on parallel single-pushout derivations. We illustrate the plug-in at several examples, some of which make use of advanced 3D features.